The WORK STRESS AND CAREER SUCCESS: THE MODERATING ROLE OF LEADER SUPPORT - Siregar, Tika (TECHNOBIZ : International Journal of Business, 2026)
Career success has become an important topic in organizational research due to its relevance for employee retention, well-being, and organizational effectiveness. Drawing on the Conservation of Resources (COR) theory, this study examines how work stress influences both objective and subjective career success, and investigates whether leader support moderates these relationships. A quantitative survey approach was applied, involving 250 employees from various startup companies in West Sumatera. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS. The findings reveal that work stress negatively and significantly affects both objective and subjective career success. Additionally, Leader support does not moderate the relationship between work stress and objective career success, but it significantly moderates the effect of work stress on subjective career success, reducing its negative impact. The study extends COR theory in the context of startups and highlights the importance of stress management programs and leadership development.